On the way to the Kingdom of Reason: Irrational Rationality of the Early Soviet Period - Rusakova, Olga F.; Rusakov, Vasiliy M.; Moiseenko, Yan Yu. (Global Journal of Cultural Studies, 2024)
The authors take a deep dive into the correlation between rational and irrational in both Enlightenment philosophy and classical Marxism, which is embodied in Russia in the form of Marxism-Leninism. The cult of Rationalism prevailed during the first years of Soviet power, which was expressed in V.I. Lenin’s academic works and was implemented into political practice. However, the established rationality resulted in the Mythology of Reason and mystification of science, which, like magic, “is capable of everything”. This kind of rationalism penetrated deeply into different forms of mass consciousness and gave birth to the irrational Kingdom of Reason, based on which all spheres of life within Soviet society were supposed to be transformed.